From Research in the Lab to Pedagogical Practices in the EFL Classroom: The Case of Task-Based Pronunciation Teaching - Joan C. Mora; Ingrid Mora-Plaza (MDPI AG, 2023)
Input and context-related factors identified by research as key success variables in L2 pronunciation development in immersion contexts play a very modest role in instructed foreign language (FL) learning environments. Scarce L2 exposure and use and L1-accented input make pronunciation learning extremely challenging. Current L2 speech learning models attribute difficulties in L2 speech acquisition to L2-to-L1 perceptual sound mappings guided by L1-based perception and poor phonological awareness and noticing of cross-language phonetic differences, which are typically not adequately addressed in instruction through pedagogic tasks. Explicit and incidental pronunciation teaching methods have been found effective at improving learners' pronunciation, but ways to integrate them into communicative approaches to language teaching are still largely unexplored. Thus, language education practices currently lack a research-informed pedagogical approach that incorporates principles of L2 speech learning and task-based language teaching (TBLT) into pronunciation instruction. This article (1) presents an outline of new avenues for research and practice in L2 pronunciation instruction and (2) reports on the findings of an empirical study that implemented a task-based pronunciation teaching (TBPT) approach to teaching a difficult L2 vowel contrast through computerized collaborative map tasks that could be easily integrated into communicative FL classrooms.